"A breath of fresh air": mindfulness training for early-career mental health social workers in Israel during COVID-19. (2nd January 2023) - Segev, Einav
ABSTRACT: The present study examined the effectiveness of participation in a mindfulness group for Israeli early career social workers during the COVID-19 period. Eleven participants conducting fieldwork in a mental health rehabilitation center were interviewed. The participants described a variety of benefits from their mindfulness training, in three main areas: (1) Personal: applying mindfulness in their daily life; (2) Family: improved work-life balance and family relationships; and (3) Professional: applying mindfulness in their work with mental health clients. Mental support and self-care tools provided to early-career social workers were perceived by the participants as helping them overcome uncertainty, fatigue, and overwork.